Penyelesaian Sengketa Gugatan Pembatalan Akad Pembiayaan Mudharabah Menurut Hukum Perdata dan Hukum Islam - Pumieda, Reyna Amalia; Astarudin, Tatang; Yusup, Deni Kamaludin (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
This research examines the dispute resolution mechanism for mudharabah contract cancellation by integrating civil law and Islamic law perspectives in Indonesia. Mudharabah contract as a sharia financial instrument requires a clear dispute resolution mechanism when cancellation occurs due to breach of contract or violation of sharia principles. The research method uses a normative juridical approach with case analysis of Supreme Court Decision Number 272 K/Ag/2015 between PT. Permodalan BV and Koperasi BS. The dispute resolution mechanism is regulated in Article 55 of Law No. 21 of 2008 with a hierarchy: deliberation, banking mediation, BASYARNAS, and religious courts. In civil law, contract cancellation is based on breach of contract (Articles 1243, 1266, 1267 of the Civil Code), while in Islamic law it occurs when the mudharib deviates from the principle of trust (KHES Articles 244, 251). The research results show legal uncertainty regarding the authority of courts versus sharia arbitration. The Supreme Court affirms the absolute competence of Religious Courts in sharia economics. Regulatory improvement and development of an effective sharia economic mediation system are needed to provide legal certainty.